2016
DOI: 10.14442/jgfm.17.1_83
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Questionnaire for Early Detection of Dementia

Abstract: Background: Patients with dementia may have already progressed to an advanced stage of illness before they receive a proper diagnosis in a medical institution. Early detection of dementia is critical, and simplified screening methods are needed to support this goal.Methods: An easy-to-complete questionnaire, consisting of 15 items that assess behaviors associated with dementia, was used for this study. Respondents were asked to fill out both the questionnaire and the Hasegawa Dementia Rating Scale-Revised (HDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…People with dementia sometimes repeatedly purchase the same items (i.e. more than necessary) due to memory impairment and disinhibition, both of which can help detect dementia . Although these features were expected to be associated with spending large amounts of money, the present findings showed that cognitive decline actually leads to reduced household spending among community‐dwelling elderly.…”
Section: Discussionmentioning
confidence: 48%
“…People with dementia sometimes repeatedly purchase the same items (i.e. more than necessary) due to memory impairment and disinhibition, both of which can help detect dementia . Although these features were expected to be associated with spending large amounts of money, the present findings showed that cognitive decline actually leads to reduced household spending among community‐dwelling elderly.…”
Section: Discussionmentioning
confidence: 48%
“…Various cognitive dysfunctions including memory, orientation, and executive functioning make it difficult for people with dementia to undertake economic activities. For instance, people with dementia sometimes repeatedly purchase the same product and are unable to calculate the change due to memory impairment [ 1 ]. Other studies have shown that cognitive dysfunction was associated with greater risk aversion related to poor financial decision-making and investments such as stockholding [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%